Targeting gut microbiota in hepatocellular carcinoma: probiotics as a novel therapy - Wan, Murphy L. Y.; El-Nezami, Hani (HepatoBiliary Surgery and Nutrition, 2018)
Hepatocellular carcinoma (HCC), the most common primary liver cancer, is one of the dreaded complications of chronic liver disease. Recent experimental and clinical studies have revealed that the alteration of gut-liver axis plays a pivotal role in the onset of chronic liver diseases, including HCC. Altered gut microbiota and endotoxemia are increasingly recognized as critical components in promoting the progression of chronic liver diseases to HCC. Probiotics have been suggested as a novel, safe and costeffective approach to prevent or treat HCC. Mechanisms by which probiotics exerts their anti-cancer effects include their ability to bind carcinogens, modulation of gut microbiota, improvement of intestinal barrier function, and immunomodulation. This review summarizes the literature findings of the changes in gut microbiota linked to HCC, and discusses the possible therapeutic implications of probiotics for HCC.